Patient-specific three-dimensional printing in cardiovascular disease - Sun, Zhonghua (2020)
Three-dimensional (3D) printing has become a widely used technique showing great promise in medical applications. In recent years, patient-specific 3D printed models are shown to play an important role in the domain of cardiovascular disease, ranging from medical education to presurgical planning and simulation of complex cardiovascular procedures, as well as development of optimal computed tomography (CT) imaging protocols. This review article provides a summary of the current applications of using 3D printed cardiovascular models with future research directions highlighted.